2021
DOI: 10.2217/fon-2021-0193
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Precautionary Practices Towards COVID-19 Among Cancer Patients

Abstract: Objective: Our study goal was to evaluate the behavioral response and practices of cancer patients to the coronavirus disease 2019 (COVID-19) pandemic in the Middle East and north Africa. Methods: A cross-sectional study was conducted using a validated anonymous 45-question survey administered via SurveyMonkey® to cancer patients in 13 centers in Algeria, Egypt, Jordan, Kuwait, Morocco and Saudi Arabia. Results: During the study period (from 21 April to 30 May 2020), 3642 patients participated in the study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…It is safe to conduct that individuals with low‐income levels would consider themselves vulnerable to the disease, and females were more responsible for their health and of course, their family health and lack of immunity to disease in individuals without a history of corona infection would cause them to adopt preventive behaviors more seriously. In this regard, previous studies also showed gender, economic status, education, and age as predictive variables 38–41 …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is safe to conduct that individuals with low‐income levels would consider themselves vulnerable to the disease, and females were more responsible for their health and of course, their family health and lack of immunity to disease in individuals without a history of corona infection would cause them to adopt preventive behaviors more seriously. In this regard, previous studies also showed gender, economic status, education, and age as predictive variables 38–41 …”
Section: Discussionmentioning
confidence: 81%
“…In this regard, previous studies also showed gender, economic status, education, and age as predictive variables. [38][39][40][41] According to the conditions created in the COVID-19 crisis, in most of the studies, according to what was done in the present study, questioning has been done online. All studies were cross-sectional and were conducted to assess current behavior.…”
Section: Resultsmentioning
confidence: 95%
“…In 2021, Jazieh et al . [ 22 ] also used a questionnaire to assess preventive measures against COVID-19 in cancer patients. The results showed that increasing the knowledge of cancer patients and taking preventive measures are needed not only to reduce the risk of infection but also to minimize interruptions in their medical care.…”
Section: Discussionmentioning
confidence: 99%
“…In one study from the region, 16% of the patients cancelled an appointment and 12% cancelled treatment sessions. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%